Survival of infiltrative hepatocellular carcinoma patients with preserved hepatic function after treatment with transarterial chemoembolization - Jang, Eun Sun; Yoon, Jung-Hwan; Chung, Jin Wook; Cho, Eun Ju; Yu, Su Jong; Lee, Jeong-Hoon; Kim, Yoon Jun; Lee, Hyo-Suk; Kim, Chung Yong (Journal of cancer research and clinical oncology, 2013)
Purpose Transarterial chemoembolization (TACE) is highly effective and safe therapeutic modality for unresectable hepatocellular carcinoma (HCC). However, the role of TACE for infiltrative HCC has never been elucidated owing to the concern about hepatic failure and subsequent mortality after the procedure. In this study, we aimed to document whether patients with infiltrative HCC would benefit from TACE. Methods Child-Pugh class A/B patients who were newly diagnosed as infiltrative HCC and treated with curative-intent TACE were enrolled. All radiological images were reviewed by a radiologist with more than 20 years of experience in TACE. Results Among 1,184 patients newly diagnosed as HCC, 233 (19.7 %) had infiltrative-type tumors and 128 (54.9 %) underwent curative-intent TACE. Although the median overall survival was 5.4 months (IQR 3.1–13.9 months) and 16 (12.5 %) patients had experienced significant complications, 19 (15.9 %) patients survived more than 2 years after the first diagnosis. In multivariable analysis, age >60 years old (HR 0.54, 95 % CI 0.31–0.92), Child-Pugh class A (HR 0.48, 95 % CI 0.30–0.76), and a major PVT without parasitic supply (HR 0.66, 95 % CI 0.44–0.99) were independent favorable prognostic factors. Development of significant complication after TACE was a significant hazard factor of survival (HR 1.99, 95 % CI 1.09–3.62). Conclusions In carefully selected patients with preserved hepatic function and good performance, TACE may achieve long-term survival of infiltrative HCC patients with major PVT without parasitic supply. However, the risk of morbidity and immediate mortality after TACE should be considered to select subjects for the procedure.